Assessment of an electronic and clinician-delivered brief intervention on cigarette, alcohol and illicit drug use among women in a reproductive healthcare clinic. (September 2019) - Forray, Ariadna; Martino, Steve; Gilstad-Hayden, Kathryn; Kershaw, Trace; Ondersma, Steve; Olmstead, Todd; Yonkers, Kimberly A.
Abstract: Background: Women are at highest risk for development of a substance use disorder during their reproductive years. We recently evaluated the efficacy of an electronic screening, brief intervention and referral to treatment (e-SBIRT) and a clinician-delivered SBIRT (SBIRT) compared with enhanced usual care (EUC) for reducing overall substance use among women recruited from reproductive health clinics. The present study assessed the impact of the SBIRT interventions within three primary substance subgroups: cigarettes, illicit drugs, and alcohol. Methods: This is a secondary analysis from a 3-group randomized trial comparing e-SBIRT and SBIRT to EUC. For the present study, participants ( N = 439) were grouped according to their primary substance: cigarettes, alcohol, or illicit drugs. Differences in days per month of primary substance use over time between treatment groups were examined using generalized estimating equations, modelling linear as well as quadratic effects of time. Results: Cigarettes were the most frequently reported primary substance ( n = 251), followed by illicit drugs ( n = 137) and alcohol ( n = 51). For primary cigarette use the interaction between the linear effect of time and treatment was significant for SBIRT (β (SE) = −0.067 (0.029), p = .020), but not e-SBIRT, suggesting greater reductions in cigarette use over the first 3 months following treatment with SBIRT compared to EUC. However, the significant interaction of SBIRT with time-squared (β (SE) = 0.009 (0.004), p = .049) showed that reductions in cigarette use attenuated over time, such that after month 3, monthly reductions in cigarette use were similar between groups. Results followed a similar pattern for primary illicit drug use among the e-SBIRT group in which the interaction of e-SBIRT treatment with linear time (β (SE) = −0.181 (0.085), p = .033) and quadratic time (β (SE) = 0.028 (0.012), p = .018) were statistically significant suggesting greater reductions in illicit drug use with e-SBIRT versus EUC, which attenuated with time. Neither SBIRT nor e-SBIRT was associated with a significant reduction in days of alcohol use per month, as compared to EUC. Conclusions: Reproductive-age women appear to respond differently to electronic- and clinician-delivered interventions, depending on their primary substance. SBIRT reduced use of cigarettes, and e-SBIRT reduced illicit drug use. Although neither intervention reduced primary alcohol use, the sample size was small ( n = 51), suggesting a need for further testing in a larger sample. Highlights: SBIRT delivered electronically or via clinician in reproductive clinics was examined. The impact of SBIRT on cigarettes, alcohol, and illicit drugs was evaluated. Clinician-delivered SBIRT reduced use of cigarettes. Electronically-delivered SBIRT reduced illicit drug use.